REDUCING WASTE IN COATED KRAFT PAPER PRODUCTION AT CV. MXX BY ADOPTING LEAN OPERATION METHOD - Gianto, Claresta
This research presents a study focused on reducing coated kraft paper waste at CV. MXX through the adoption of lean operation methods. The objective of this research is to find the root cause of the high waste percentage in CV. MXX production process and suggest the appropriate solution for waste reduction. The problem faced by CV. MXX has a high waste rate in the production process. According to the CV. MXX owner's observation, waste product in CV. MXX has reached a staggering 9% of the total production volume. This number is relatively high, as it can reach up to 7 tons of waste daily, which translates into IDR 64,000,000 of loss value. This research adopts a mixed-methods approach, combining quantitative data analysis and qualitative observations. Statistical Process Control (SPC) charts are utilized for quality measurement then further analyzed with the rule of seven for control charts. The data collection indicates that the waste generation is triggered by unstandardized operation, lack of quality control, and large product variability. Overall, this research is expected to give sustainable suggestions in the effort of waste reduction, production efficiency, product quality, and staff involvement in waste reduction initiatives. Based on the analysis, this paper suggests increasing control in product quality by establishing a formal and systematic Standard Operating Procedure (SOP), also an additional monitoring phase in every major production stage.